Room temperature synthesis of stable single silica-coated CsPbBr3 quantum dots combining tunable red emission of Ag–In–Zn–S for High-CRI white light-emitting diodes. (January 2020) - Guan, Hongling; Zhao, Shuangyi; Wang, Huaxin; Yan, Dongdong; Wang, Ming; Zang, Zhigang
Abstract: White light emitting diodes (WLEDs) based on all-inorganic halide (CsPbX3, X = Cl, Br and I) perovskite quantum dots (QDs) have attracted broad attention due to their high brightness. However, their poor stability and anion-exchange reaction when utilized together are still the main challenges that impede their applications. Herein, a one-step in situ method under room temperature in air is proposed to synthesize CsPbBr3 QDs coated with SiO2 (CsPbBr3 @SiO2 ), where the whole process takes only 20 s. The as-prepared CsPbBr3 @SiO2 QDs samples present an enhanced stability in the thermal and polar-solvent environment, maintaining its high photoluminescence quantum yield (PLQY~75%). Thereby WLEDs are constructed by combining CsPbBr3 @SiO2 with red Ag–In–Zn–S QDs on InGaN blue chip, achieving a high color rendering index (CRI) of 91, a correlated color temperature (CCT) of 3689 K and a power efficiency of 40.6 lm W −1 . Graphical abstract: Image 1 Highlights: One-step in situ synthesis of SiO2 coated CsPbBr3 QDs under room temperature in air is proposed. The coated CsPbBr3 QDs exhibit higher stability and PLQY, in comparision with pure CsPbBr3 QDs. The obtained CRI value of 91 is the highest one among the reported perovskites WLEDs.